2023
DOI: 10.3390/vaccines11020207
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study to Assess mRNA-COVID-19 Vaccine Safety among Indian Children (5–17 Years) Living in Saudi Arabia

Abstract: The objective of this study is to assess the frequency and severity of adverse events following immunization (AEFI) in Indian children aged 5–17 years who received the Pfizer-BioNTech mRNA COVID-19 vaccine, as well as to investigate for predictors of AEFI. To examine AEFI following the first and second doses of Pfizer’s vaccine, semi-structured questionnaires were distributed as Google forms at Indian schools in Saudi Arabia. The 385 responses included 48.1% male and 51.9% female children, with 136 responses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Most of the individuals in the lower social class are on a daily wage and they cannot afford to miss a single day at work in an already financially turbulent situation. Moreover, the lack of access to social help groups and a lack of information about free vaccination drives and how to book a slot were factors that interplayed and thereby affected the decision of vaccination [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the individuals in the lower social class are on a daily wage and they cannot afford to miss a single day at work in an already financially turbulent situation. Moreover, the lack of access to social help groups and a lack of information about free vaccination drives and how to book a slot were factors that interplayed and thereby affected the decision of vaccination [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parents who believe that the perceived risk of their children contracting an infectious disease is lower than the perceived risk of vaccine efficacy are more likely to refuse vaccinations. It has also been observed that the adverse effects following vaccination among children who received the Pfizer-BioNTech mRNA COVID-19 vaccine were reportedly mild, mainly presenting as local reactions such as pain, swelling, and redness at the injection site (22%); low-grade fever (15.6%); high-grade fever (1.8%); and rhinorrhea (1%) [ 29 ]. Therefore, government organizations must effectively inform, educate, and communicate with parents to reduce the impact of negative information from varied online sources [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%